2016
DOI: 10.1371/journal.pone.0151866
|View full text |Cite
|
Sign up to set email alerts
|

Varying Patterns on Varying Scales: A Metacommunity Analysis of Nematodes in European Lakes

Abstract: Ecological community patterns are often extremely complex and the factors with the greatest influence on community structure have yet to be identified. In this study we used the elements of metacommunity structure (EMS) framework to characterize the metacommunities of freshwater nematodes in 16 European lakes at four geographical scales (radius ranging from 80 m to 360 km). The site characteristics associated with site scores indicative of the structuring gradient were identified using Spearman rank correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…3, 'specialization'). Studies on meiofauna metacommunities that included different spatial scales found that the relevance of species sorting was scale-dependent, becoming less significant on larger scales, where dispersal-based processes seemed to dominate (Matsuda et al 2015, Dümmer et al, 2016, which is in accordance with general expectations (Leibold & Chase, 2018).…”
Section: Niche-based Processessupporting
confidence: 81%
See 3 more Smart Citations
“…3, 'specialization'). Studies on meiofauna metacommunities that included different spatial scales found that the relevance of species sorting was scale-dependent, becoming less significant on larger scales, where dispersal-based processes seemed to dominate (Matsuda et al 2015, Dümmer et al, 2016, which is in accordance with general expectations (Leibold & Chase, 2018).…”
Section: Niche-based Processessupporting
confidence: 81%
“…Some bdelloid rotifers were found to be significantly associated with different habitat types, i.e., lotic, lentic, and terrestrial mosses , different substrate types (mosses vs. lichens; , and particular lichen species (Fontaneto et al, 2011). The nematode metacommunity in lakes responded to trophic state, indicative of bottom-up structuring of these communities (Dümmer et al, 2016).…”
Section: Niche-based Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…The metacommunity in a region becomes a key element when considering local species richness in fragmented habitats (Leibold et al, 2004). However, it is not always easy how to disentangle the relative effects of purely spatial factors from environmental influences; particularly, because the biodiversity patterns may be the result of the spatial scale of analysis when studying community assemblages (Chase, 2014;Dümmer, Ristau, & Traunspurger, 2016;Heino, 2011). In this context, comparing patterns of species distribution between different groups of organisms, with varying dispersal capabilities and environmental tolerances, is an approach to empirically evaluate whether environment prevails over spatial factors in determining the biodiversity patterns at a particular spatial scale (Heino, 2013;Heino & Peckarsky, 2014;Mantyka-Pringle, Martin, & Rhodes, 2013;Urban, Tewksbury, & Sheldon, 2012).…”
Section: Introductionmentioning
confidence: 99%